Iono-Elastomer-Based Wearable Strain Sensor with Real-Time Thermomechanical Dual Response - Xie, Yunsong; Xie, Ru; Yang, Hao-Cheng; Chen, Zhaowei; Hou, Jingwei; López-Barrón, Carlos R; Wagner, Norman J; Gao, Kai-Zhong (ACS applied materials & interfaces, 2018)
An ultrastretchable iono-elastomer with resistance sensitive to both elongation strain and temperature has been developed by hierarchical self-assembly of an end functionalized triblock copolymer in a protic ionic liquid (ethylammonium nitrate) followed by cross-linking. Small-angle X-ray scattering experiments in situ with uniaxial elongation reveal a nanoscale microstructural transition of the hierarchically self-assembled cross-linked micelles that is responsible for the material’s remarkable mechanical and ionic conductivity responses. The results show that the intermicelle distance extends along the deformation direction while the micelles organize into a long-range ordered face-centered-cubic structure during the uniaxial elongation. Besides good cyclability and resistance to selected physical damage, the iono-elastomer simultaneously achieves an unprecedented combination of high stretchability (340%), highly linear resistance vs elongation strain (R 2 = 0.998), and large temperature gauge factor (ΔR/R = 3.24%/°C@30 °C). Human subject testing demonstrates that the iono-elastomer-based wearable thermomechanical sensor is able to effectively and accurately register both body motion and skin temperature simultaneously.